School-based literacy policy research (2014–2024): global trends, networks, and thematic developments - Cahyani, Anita; Slamet, Sty; Sudiyanto, Sudiyanto (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Despite the increasing global emphasis on literacy education, school-based literacy policies continue to face challenges in their development, implementation, and effectiveness. However, research examining these policies remains fragmented, particularly regarding their thematic evolution and geographic distribution. This study aims to analyze the research trends, thematic developments, and collaboration patterns in school-based literacy policy research from 2014 to 2024 through a bibliometric analysis. Using the Scopus database, 781 research articles were analyzed with VOSviewer and R Bibliometrix to identify citation structures, co-authorship networks, and thematic clusters. The findings reveal four major research clusters: (1) pedagogical approaches and teacher professional development, (2) health and well-being, including mental health literacy, (3) basic literacy skills and language development, and (4) policy implementation and evaluation. Over the past decade, publication output increased from 20 articles in 2014 to over 60 in 2023-2024, reflecting a growing academic interest in school-based literacy policies. The citation analysis shows that highly cited studies often focus on the intersection of literacy, digital transformation, and student well-being, indicating a shift toward a more integrated policy framework. Collaboration analysis highlights strong research networks among institutions in North America and Australia, though representation from developing regions remains limited. These findings provide critical insights for policymakers and educators in designing holistic literacy policies that integrate pedagogy, digital literacy, and mental health considerations. By applying bibliometric methods to literacy policy research, this study offers a novel, data-driven perspective on the field’s evolution and highlights directions for future research.